The Influence of Work Environment and Work-Life Balance on Employee Job Satisfaction through Organizational Culture at the Post Office of Bali - Lestari, Ni Komang Yunita Diah; Merta, I Ketut; Widhiantara, I Kadek (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to examine the influence of the work environment and work-life balance on employee job satisfaction through organizational culture at the Bali Regional Post Office, using the grand theory of Human Resource Management (HR). The study employs a quantitative associative method, utilizing a questionnaire with a population of 114 and a sample of 50 respondents, calculated using the Slovin formula. Five hypotheses were tested, and data were processed with SPSS Version 24. The research findings indicate that: 1. The work environment has a negative and insignificant effect on employee job satisfaction; 2. Organizational culture has a positive and significant effect on employee job satisfaction; 3. Work-life balance has a positive and significant effect on employee job satisfaction; 4. Work-life balance has a positive but insignificant effect on organizational culture; 5. Organizational culture can mediate the relationship between the work environment, work-life balance, and employee job satisfaction. The implications of this research suggest that the effects of the work environment, work-life balance, and organizational culture on employee job satisfaction at the Bali Regional Post Office are moderate. Additionally, it shows that organizational culture can mediate the relationship between the work environment and work-life balance in terms of employee satisfaction.